METODE FULL COSTING DAN COST PLUS DALAM HARGA JUAL USAHA MIKRO KECIL DAN MENENGAH - Gerlan Haha Nusa; David Sulistiyantoro; Puji Winar Cahyo; Inna Zahara; Arif Himawan (Journal of Economic, Bussines and Accounting (COSTING), 2026)
The problem faced by MSMEs is the lack of recording the costs incurred in determining prices. The aim of the research is for MSMEs to find out the cost of production using the full costing method and determine the desired profit using the cost-plus approach. With this determination, it is hoped that it can be used to make various decisions regarding selling prices. The research method used is descriptive qualitative to analyze the data. The research results show that the selling price of beverage products at full costing and cost-plus is lower than the price determined by Omah Pakis. Meanwhile, for food products, the full costing and cost-plus calculations are higher compared to the prices determined by Omah Pakis. The conclusion of this research is that costs are only charged to the elements of raw material and labor costs so that the information on determining selling prices is incomplete. As a result of incomplete cost information data being available, the decisions taken by the owner of Omah Pakis only focus on the short term. Omah Pakis can group production costs by determining the markup to determine the selling price using the cost-plus method.